Evaluation of Real-Time PCR Coupled With Multiplex Probe Melting Curve Analysis for Pathogen Detection in Patients With Suspected Bloodstream Infections - Xiao, Yao; Shen, Xu; Zhao, Qi-Feng; Yao, Yi-Hui; Yang, Tian-Ci; Niu, Jian-Jun (Frontiers in Cellular and Infection Microbiology, 2019)
Background: This study aimed to evaluate real-time polymerase chain reaction coupled with multiplex probe melting curve analysis (PCR-MCA) for pathogen detection in patients with suspected bloodstream infections (BSIs). Methods: A PCR-MCA assay was developed for simultaneous identification of 28 kinds of the most common pathogens and two resistance genes within a few hours. The diagnostic performance of the PCR-MCA assay was determined and compared to the results of blood culture. Results: A total of 2844 consecutive new episodes of suspected BSIs in 2763 patients were included in this study. There were 269 episodes of pathogens identified by blood culture. For all the pathogens tested, the PCR-MCA assay exhibited a sensitivity of 88.8% (239/269), specificity of 100% (2575/2575), and agreement of 98.9% (2814/2844). For the pathogens on the PCR-MCA list, the PCR-MCA results had a sensitivity of 99.2% (239/241), specificity of 100% (2575/2575), and agreement of 99.9% (2814/2816) compared with the results of blood culture. For seven samples with multiple pathogens identified simultaneously during one blood culture investigation, the PCR-MCA assay verified the results of the blood culture, with an agreement rate of 100% for each. Conclusion: The PCR-MCA assay could discover 88.8% of the pathogens in clinical practice, showing excellent diagnostic performance versus that of blood culture for pathogen detection in patients with suspected BSIs, and would contribute to rapid diagnosis and correct antibiotic administration.